Farmers' perspective on herbicide‐resistant weeds and application of resistance management strategies: results from a German survey. Issue 10 (1st February 2018) - Ulber, Lena; Rissel, Dagmar
Abstract: BACKGROUND: A herbicide resistance survey was conducted in Germany to determine farmers' awareness of herbicide resistance and experience with resistant weeds, the information sources on herbicide resistance used and the methods employed to confirm resistance. In addition, the application pattern and perception of resistance management strategies by farmers were assessed. RESULTS: The majority of farmers (88%) were aware of the presence of herbicide resistance cases in Germany and 64% and 50% of farmers reported that resistant weeds had been detected in their county and on their farm, respectively. Resistance management strategies were reported to be applied by 87% of the farmers and three clusters of different resistance management approaches used to minimize the evolution of resistant weed populations were identified and linked to farmers' perception of resistance and farm management characteristics. When asked about obstacles to adopting resistance management strategies, higher cost was the obstacle most cited by farmers, followed by weather and labour intensity/labour costs. CONCLUSION: Outcomes from this survey may help researchers and crop consultants to increase understanding of farmers' perception of herbicide resistance issues, to improve knowledge dissemination concerning herbicide resistance and to develop resistance management programmes with high agronomic practicability and acceptance by farmers. © 2017 Society of Chemical Industry Abstract : A survey was conducted to determine farmers' awareness of herbicide resistance and resistance management approaches used to minimize the evolution and spread of resistant weed populations.